Temporal bone metastasis - A clinical case - Decq Mota, Sofia (2014)
The bone metastasis to the head and neck is rare. In 20-35% of cases, can be the first manifestation of an occult neoplasia. In the specific case of the Temporal Bone, metastases originate most often from the breast, lung, kidney, prostate and stomach. We report the case of a patient, female, 71 years, with the diagnosis of Ductal Carcinoma Cribiform type in the left breast, having undergone total mastectomy, chemotherapy and radiotherapy. She presented with left otalgia and ipsilateral hemifacial palsy, without other otologic symptoms. It was diagnosed Complicated Chronic Otitis Media, she was medicated and Computed Tomography ordered, wich demonstrated an exuberant thickening of the epicranial soft parts with extension to the ispilateral external auditory channel. For worsening symptoms, the patient was admitted to the Otorhinolaryngology Service of this hospital for administration of intravenous treatment, and it was hypothesized the diagnosis of malignant external otitis. For maintenance of the frame, despite optimal therapy, she was subjected to surgical intervention and performed temporal biopsy that diagnosed metastatic lesions of invasive breast carcinoma.